Projeto de impregnadora a vácuo para manutenção de estatores em motores elétricos - Portela, Guilherme (2024)
Impregnation involves submerging a part in resin or varnish to improve the component's resistance, durability, and mechanical properties. This process is applied to porous parts such as electronic components, ceramics, composites, and metal parts. The present final paper aims to develop a vacuum impregnator project for impregnating stators in electric motors, with an affordable cost and the capability to facilitate and enhance the stator coil impregnation process in electric motors. That will reduce the chances of rework or warranty maintenance, and consequently minimizing waste for the company performing this type of maintenance. The study included market research to gather the necessary components for the project and their specifications, in addition to developing the project using Autodesk Inventor software. After a technical and economic analysis, it was found that the designed machine has a total estimated cost between R$ 20,000.00 and R$ 25,000.00, representing a substantial saving of 75% to 80% compared to the existing machine on the market provided by the company Vacuolu, whose cost is approximately R$ 100,000.00. Moreover, the replacement of manual valves with solenoid valves contributed to system automation, facilitating operation and potentially increasing the efficiency and accuracy of the impregnation process. This technological advancement may result in higher quality final products and increased productivity. Therefore, the construction of a vacuum impregnator for electric motor stators as presented in the project is not only feasible but also advantageous from an economic and operational standpoint. The implementation of this project can provide companies in the electric motor maintenance industry with a more affordable and efficient solution, promoting technological innovations and optimizing financial and productive resources.